On Aquinas's Theological Reliabilism - Di Ceglie, Roberto (Heythrop journal, 2018)
In an essay titled Aquinas on the Foundations of Knowledge, Eleonore Stump rejects the idea that Aquinas's epistemology is foundationalist. I agree with Stump, and share in her conviction that the Angelic doctor developed instead what can be seen as a kind of theological reliabilism. In this article, I intend to take her position a step further. First, I would like to show that Thomistic reliabilism falls into a vicious circle if seen as based on a merely rational theism. Second, I am going to argue that for Aquinas such reliabilism depends instead on Christian faith, construed as the act of believing the revealed truth by virtue of the love relationship that God allows human beings to have with him.